Correction to: Integrating isotopic, microbial, and modeling approaches to understand methane dynamics in a frequently disturbed deep reservoir in Taiwan. Issue 5 (29th March 2018) - Itoh, Masayuki; Kojima, Hisaya; Ho, Pei‐Chi; Chang, Chun‐Wei; Chen, Tzong‐Yueh; Hsiao, Silver Sung‐Yun; Kobayashi, Yuki; Fujibayashi, Megumu; Kao, Shuh‐Ji; Hsieh, Chih‐hao; Fukui, Manabu; Okuda, Noboru; et al.
Abstract : The article "Integrating isotopic, microbial, and modeling approaches to understand methane dynamics in a frequently disturbed deep reservoir in Taiwan", written by Masayuki Itoh, Hisaya Kojima, Pei‐Chi Ho, Chun‐Wei Chang, Tzong‐Yueh Chen, Silver Sung‐Yun Hsiao, Yuki Kobayashi, Megumu Fujibayashi, Shuh‐Ji Kao, Chih‐hao Hsieh, Manabu Fukui, Noboru Okuda, Takeshi Miki, Fuh‐Kwo Shiah, was originally published electronically on the publisher's internet portal (currently SpringerLink) on 18 September 2017 without open access.